The Security Rating on Local Ablation and Interventional Therapy for Hepatocellular Carcinoma (HCC) and the Comparison among Multiple Anesthesia Methods - Qianhui Jin; Xinhua Chen; Shusen Zheng (Analytical Cellular Pathology)
Recently, the interventional therapies are used more often in clinical practice for hepatocellular carcinoma. The most commonly used methodologies include radiofrequency ablation, microwave ablation, laser ablation, and cryotherapy. Most of the interventional operations need local anesthesia combined with intravenous sedation. Also, some interventional therapy centers apply general anesthesia. However, different anesthesia methods can cause diverse effects on patients’ pain management, recovery time, and hospitalization time. For the better understanding of the current anesthesia application status, we summarize and analyze multiple anesthesia methods while being applied in interventional therapy for hepatocellular carcinoma; in addition, their characters are also compared in this paper.